Endophyte-Infected Tall Fescue Affects Rumen Microbiota in Grazing Ewes at Gestation and Lactation - Chai, Jianmin; Alrashedi, Saleh; Coffey, Ken; Burke, Joan M.; Feye, Kristina; Ricke, Steven C.; Park, Si Hong; Edwards, J. Lannett; Zhao, Jiangchao (Frontiers in Veterinary Science, 2020)
Tall fescue (Schedonorus arundinaceus) is a cool-season perennial grass that is widely used as a forage for many livestock species including sheep. An endophyte (Neotyphodium coenophialum) in tall fescue produces ergot alkaloids that enhance plant survival but produce toxicosis in animals. The objective of this study was to investigate the rumen microbiota from gestation and lactation in ewes grazing tall fescue pastures with high (HA) or moderate (MA) levels of endophyte infection, and their relationship with serum parameters. Data were collected at the beginning of the study (d1), the week before initiation of lambing (d51), and at the end of the trial (d115). The rumen microbiota was evaluated using 16S rRNA gene sequencing. Ewes grazing HA had greater serum non-esterified fatty acid (NEFA) (P = 0.024) levels compared with ewes in MA pasture at d115. Both the number of observed OTUs and Shannon diversity index tended (P = 0.08, P = 0.06) to be greater for HA than for MA on d115. At the genus level, Prevotella relative abundance increased with time in both MA and HA (on d1, d51 and d115: 15.17%, 25.59% and 24.78% in MA; 14.17%, 18.10% and 19.41% in HA). Taxa unclassified at the genus level including (unclassified) Lachnospiraceae, Coriobacteriaceae and Veillonellaceae exhibited higher abundances in HA at d51 (3.72%, 2.07% and 11.22%) compared with MA (2.06%, 1.28% and 7.42%). The predictor microbiota for HA and MA were identified by a random forest classification model. The HA predictors included bacteria associated with unclassified Coriobacteriaceae and Ruminococcaceae. Other OTUs classified as Prevotella and Clostridiales could be microbial predictors for MA. The OTUs classified as Prevotella and Lachnospiraceae were negatively correlated with serum concentration of prolactin. Negative correlations with NEFA were observed in the microbiota such as species affiliated to unclassified Clostridiales and Prevotella. OTUs classified as Bacteroidetes and Coriobacteriaceae exhibited a positive correlation with NEFA. Our study confirmed that the rumen microbiota populations were affected by high levels of toxins in endophyte-infected tall fescue and were associated with host hormone and energy metabolism.